Prevocational training situation of young people with special educational needs (SEN) in Germany - Ursula Spichtinger; Aistė Valaikienė (Social Welfare: Interdisciplinary Approach, 2012)
The article presents the analysis of educational situation of young people with Special Educational Needs (SEN) in Germany based on the example of Prevocational Training in a Vocational Training Institute. German Federal Law is discussed in the context of Germany Federal States regulations that have their own cultural sovereignty. Systems of special and regular education, performing vocational training and prevocational counselling are discussed in parallel with pupils having special educational needs education and preparation for the labour market relationships. Case of Vocational Training Institute Kirchseeon/Berufsbildungswerk Kirchseeon (BBW Kirchseeon) refects compatibility of the needs of individual pupils with SEN and possibilities to get into labour market and general state regulations. On this basis, vocational education has the task to fnd ways for a precisely ftting promotion.